Menstrual abnormalities and their association with lifestyle pattern in adolescent girls of Garhwal, India - Negi, Priyanka (J Family Med Prim Care, 2018)
BACKGROUND: This study tried to find out the prevalence of menstrual abnormalities in adolescent girls and their association with dietary and exercise pattern in Garhwal region of India. MATERIALS AND METHODS: In this study, cross-sectional questionnaires survey was conducted in different schools of Garhwal. These questionnaires were based on socioeconomic data, dietary and physical activities, and menstrual abnormalities. RESULTS: The age of menarche was 13.5 ± 0.64 years. Dysmenorrhea (62.75%), premenstrual syndrome (PMS) (40.42%), and irregular cycle (28.72%) were observed common problems among adolescent girls. The result showed that dysmenorrhea, PMS, and menstrual irregularities were directly associated with dietary habits and physical activities. Dysmenorrhea was associated with eating junk food (66.10%), and PMS was associated with lacking of physical activities (78.94%). CONCLUSION: The result suggests that feeding habit and physical activities directly affecting the menstrual health of adolescent girls.